Pendanaan Kampanye Pemilihan Kepala Daerah oleh Negara dalam Perspektif Kejahatan Korporasi - Sulistiorini, Yayuk Dwi Agus (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze regional head election campaigns as a form of implementing democracy and regional head election campaign funds from the perspective of corporate crime. This study used a type of normative juridical research with a conceptual approach, statutory approach, and historical approach. Source of data used in the form of secondary legal materials. Data analysis used a qualitative descriptive technique. The study results showed that the regional head election campaign aimed to bring the community closer to the dynamics of democracy. The General Election Commission could facilitate regional head election campaign activities at the Provincial and Regency/City levels. The government's policy regarding funding campaigns for pairs of regional head candidates using the Regional Expenditure Budget in Article 65 paragraph (2) of the Regional Head Election Law was an irrelevant action. It could be categorized as the state has committed a covert corporate crime.